Representation and production of the genius loci in literature - Stojmenska-Elzeser, Sonja (Primerjalna književnost, 2013)
This paper focuses on the problems that lie at the intersection of cultural geography, literary studies, and ecocriticism. It is concerned with the relationship between human creativity and the physical world that we all live in and pass through. Space is not merely a physical notion, but also largely acultural construct. This double movement of representing and creating, or constructing, a specific place is a continuous process in which the arts and literature play an important role.
Keywords: kulturna geografija; prostor; literarna pokrajina; genius loci; literarne študije